(3GdeLjO aj EYLGR GdbQGf GdeLjOs - (3GdRedcGfj , ceGd GdOjf CHh GdecGQe YHO GdhGMO GdSeGcj, GdRedcGfj,J (B651 (3g` s ((3eMehO Hf GSeGYjd Hf Ydi Hf MHT GdQHYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf eHTQkG hfPjQkG hHYO aEf cJGHi GdeJQLe HGdJHjGf ai Yde GdHjGf YXeJ ahGFOg s
(3BNQgG (B:s
(3hCeG Yde GdQDjG hGdQbi adjS MeG JJhba YdjgeG GdYdhe GdTQYjI hEf CTGQ CdjgG GdbQBf agPG HjGf GfbSGe GdYdhe efg hJTYHgG hgPG BNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQM hGNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B209s
Keywords: (3GdHdGZIs